Postepy w leczeniu nerkozastępczym w Polsce i na świecie - Rutkowski, Bolesław (Przewodnik Lekarza/Guide for GPs, 2010)
Renal replacement therapy which include dialysis and renal transplantation enable saving many lives during last fifty years. Currently over 2 milion people are treated using this kind of therapy throughout the world. Unfortunately big disproportion is existing in availability of renal replacement therapy between developed countries and these which are still having political and economical problems. In this first group, where Poland is located from the turn of centuries this type of therapy is available to all patients with end stage renal disease. In the second group where big countries with huge populations are present, like China, India, Russia and vast majority of African countries, availability of renal replacement therapy is still limited. Nevertheless even in these regions significant progress is visible in this matter. It seems to be very important taking into account fact that renal replacement therapy with use of modern technologies is not only able to secure better survival but also high quality of life.